PENGARUH TOTAL ASSET TURNOVER (TAT), DAN LONG-TERM DEBT TO EQUITY RATIO (LTDER) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI BEI - Annisa Apriyani; Nurul Huda; M.Rimawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2026)
This study aims to analyze the effect of Total Asset Turnover (TAT) and Long-Term Debt to Equity Ratio (LTDER) on Return on Assets (ROA) as an indicator of financial performance in consumer goods subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This research uses a quantitative approach with an associative method. The sample consists of four manufacturing companies in the food and beverage subsector selected through purposive sampling. Data were obtained from annual financial reports and analyzed using multiple linear regression with SPSS version 26. The results show that both TAT and LTDER have a significant partial effect on ROA. Simultaneously, these variables also have a significant impact on ROA. These findings indicate that asset utilization efficiency and long-term financing structure play a crucial role in determining company profitability. This study provides practical implications for company management and investors in making strategic decisions and managing financial structure